Multi‐scalar Labour Agency in Global Production Networks: Contestation and Crisis in the South African Fruit Sector. Issue 4 (9th June 2017) - Alford, Matthew; Barrientos, Stephanie; Visser, Margareet
ABSTRACT: Integration into global production networks poses significant challenges, and also opens up opportunities, for labour agency. Governance by lead firms affects working conditions and can drive precarious employment; this interacts with and can constrain national labour legislation covering labour rights. The global production networks (GPN) approach facilitates examination of commercial value chains, their interaction with institutionally and societally embedded labour markets, and potential leverage points for labour contestation transcending local, national and global scales. This informs analysis of commercial/societal articulations as contested processes opening space for multi‐scalar labour agency within global production networks. This article examines how tensions between global commercial and societally embedded dimensions of global production networks drive precarious work, and seeks to understand the implications for emergent forms of multi‐scalar community‐based labour agency. These questions are explored through an examination of labour casualization and contestation in South African fruit production in 2012–13, using the GPN approach. The authors find that multi‐scalar channels of labour agency leveraging both global commercial and government actors can enable reworking by unorganized community‐based labour to bargain for better pay and conditions, but if the underlying global commercial logic is to be challenged, more systemic strategies are required.